Lubrication Practices and Receptive Anal Sex: Implications for STI Transmission and Prevention - Austin Lee, BA; Thomas W. Gaither, MD, MAS; Marvin E. Langston, PhD, MPH; Stephanie E. Cohen, MD, MPH; Benjamin N. Breyer, MD, MAS (Sexual Medicine, 2021)
Introduction: Implications of lubricant use in men having sex with men (MSM) are poorly characterized, particularly associations with sexual behavior and rectal sexually transmitted infection (STI) risk. Aim: We sought to clarify covariates associated with lubrication type including differing sexual preferences and rectal STI prevalence. Methods: Primary English-speaking individuals ≥18 years old visiting San Francisco City Clinic (SFCC) between April and May of 2018 who endorsed lubricant use during receptive anal sex within the last 3 months were studied. Associations between lubrication type used and collected covariates were assessed using Kruskal-Wallis analysis of variance for continuous variables and Chi-squared test for categorical variables. We used logistic regression to examine the association between lubrication type and rectal STI test result. Main Outcome Measures: Rectal STI test positivity. Results: From all enrolled participants, 179 completed the survey and endorsed use of a lubricant during receptive anal sex within the last 3 months. Silicone lubricant users had the most sexual partners in the last 3 months (13 [mean] ± 30 [SD], P= .0003) and were most likely to have a history of gonorrhea. Oil-based lubricant users had the most partners with whom they had receptive anal sex in the last 3 months (7 ± 6, P= .03). Water-based lubricant users most commonly used a condom in their last sexual encounter and had the fewest sexual partners in the last 3 months (4 ± 4, P= .0003). Spit/saliva lubricant use was associated with positive rectal STI result. Conclusion: Silicone and oil-based lubricant users were more likely to report condomless receptive anal sex and to have a history of gonorrhea while spit/saliva lubricant use associated with positive rectal STI acquisition. Lee A, Gaither TW, Langston ME, et al. Lubrication Practices and Receptive Anal Sex: Implications for STI Transmission and Prevention. Sex Med 2021;9:100341.